Shear performance and failure process of perfobond connector in steel-UHPC composite structures. (April 2023) - Liu, Yangqing; Yang, Haiyan; Luan, Liujie; Liu, Yuqing; Du, Xiaoqing
Abstract: Nowadays, the application of Ultra-High Performance Concrete (UHPC) provides innovative concepts for structural designs of composite structures. Perfobond connectors (PBLs) with excellent shear capacity and fatigue performance may fully use the superiority of UHPC and thus are increasingly adopted in various novel steel-UHPC composite structures. However, the shear behavior and failure modes of PBLs embedded in UHPC slabs still need to be clarified. Therefore, this paper aims to evaluate the shear performance and further propose an equation for the shear capacity of UHPC PBLs. Firstly, six standard push-out tests taking the hole diameter, hole height, and whether perforated rebar was used as the parameters were performed. Subsequently, a detailed finite element (FE) model for the push-out test was established and validated by the test results, which took the fracture of perforated rebars into account by introducing the LW fracture criterion. Further, a parametric study was carried out to clarify the effects of dowel area, rebar sectional area, and hole shape. The results showed that benefiting from the high rigidity of UHPC, the PBLs with perforated rebars presented a slip-hardening behavior and excellent ductility. The slip corresponding to the rebar fracture grew with the rebar and hole diameter. Besides, the shear stiffness markedly rose with the hole diameter and height, while the effect of perforated rebars on shear stiffness was relatively small. Finally, the shear capacity equations for long-hole PBLs embedded in UHPC were proposed. The calculated results matched well with the 80 numerical and 21 collected experimental results.